Resolving the trade comovement puzzle at the margin of global value chains - Bongseok Choi (International Trade, Politics and Development)
Purpose – This paper investigates the crucial role that the trade of intermediate goods plays in elucidating trade-output synchronization. We specifically highlight the significance of incorporating intermediate trade, particularly concerning the dominance of forward linkages in the global value chains (GVCs) of countries producing intermediate goods. Design/methodology/approach – We extend Johnson (2014) international real business cycle (IRBC) model to integrate the foreign value added by intermediate exporters within a forward-linkage GVC. Findings – Model simulations indicate that the trade of intermediate goods accounts for around 31–33% of observed trade-output synchronization. Notably, the inclusion of value-added rents in GVCs within intermediate goods trade boosts the explanatory power to 55%. Research limitations/implications – Although adding input trade information does not replicate the empirical finding enough to resolve the trade-comovement puzzle within the IRBC-style framework, as Johnson (2014) pointed, this might highlight the limitations of the framework itself. The limitations of both our work and Johnson (2014) suggest that a more endogenous mechanism that correlates comovement with trade independently of the correlation between trade and comovement of TFPs should be introduced in the IRBC model. Originality/value – Our paper extends Johnson (2014) IRBC model to incorporate the foreign value added to intermediate trade within forward-linkage GVCs. The model’s explanatory power in resolving the trade comovement puzzle has improved.